Optimal level of purple acid phosphatase5 is required for maintaining complete resistance to Pseudomonas syringae - Ravichandran, Sridhar; Stone, Sophia; Benkel, Bernhard; Zhang, Junzeng; Berrue, Fabrice; Prithiviraj, Balakrishnan (Frontiers in Plant Science, 2015)
Plants possess an exceedingly complex innate immune system to defend against most pathogens. However, a relative proportion of the pathogens overcome host’s innate immunity and impair plant growth and productivity. We previously showed that mutation in purple acid phosphatase (PAP5) lead to enhanced susceptibility of Arabidopsis to the bacterial pathogen Pseudomonas syringae pv tomato DC3000 (Pst DC3000). Here, we report that an optimal level of PAP5 is crucial for mounting complete basal resistance. Overexpression of PAP5 impaired ICS1, PR1 expression and salicylic acid (SA) accumulation similar to pap5 knockout mutant plants. Moreover, plant overexpressing PAP5 was impaired in H2O2 accumulation in response to Pst DC3000. PAP5 is localized in to peroxisomes, a known site of generation of reactive oxygen species for activation of defense responses. Taken together, our results demonstrate that optimal levels of PAP5 is required for mounting resistance against Pst DC3000 as both knockout and overexpression of PAP5 lead to compromised basal resistance.